Flipped Classroom sebagai Solusi Mutakhir untuk Pembelajaran Berbasis Digital Masa Kini: Flipped Classroom as the Cutting-edge Solution for Today’s Digital-based Learning - Maharani, Anak Agung Putri; Pramerta, I Gde Putu Agus; Widhiasih, Luh Ketut Sri; Maba, Wayan; Wardana, I Ketut (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Along with technological developments in the world of education, teachers are expected to always learn and adapt to technological developments so that the learning process in the classroom is more interesting. Apart from that, the teacher's ability to master and apply competencies in the field of technology, especially in the field of education, can help teachers develop learning materials and media so that they are always relevant to current developments. However, problems were found faced by teachers at the SMK Pariwisata Kertayasa Singakerta Ubud where their competence regarding the use of technology and teaching techniques was still not optimised. For this reason, the community service team provided the solutions that can be implemented by the community service team to solve the problems faced by partners. There is a solution that has been agreed upon, namely conducting socialization, training, and assistance in implementing the Flipped Classroom for the teachers as community service participants. The results of this community service activity show an increase in the teacher’s knowledge and understanding of implementing Flipped Classroom. Moreover, they gave a positive response to the activities provided by the community service team.